Lung Sounds and the Stethoscope - a Lung Sounds Primer - David Cugell; Noam Gavriely; Dan Zellner (Association of American Medical Colleges, 2012)
Abstract A major difficulty for novice students when learning how to use a stethoscope for the interpretation of breath sounds is auscultatory identification of the phases of the breathing cycle. This is particularly true when listening to recorded material rather than a live patient. To overcome this obstacle a combined graphic-acoustic presentation has been developed. This module contains a web-based presentation including sounds from the lungs, as heard with a stethoscope, from patients with various lung diseases and normal subjects. A four-step procedure for listening to and analyzing lung sounds is described in detail. In addition to the customary narrative explanations, chest X-ray film images, graphic displays of the acoustic signal, and animation are used. Physiological explanations are included with the self-test questions. The resource concludes with a set of nine lung sounds that students can use to assess their competence and ability to recognize abnormal lung sounds. Dynamic movement of a thorax, a moving cursor that identifies at what point in the breathing cycle the sound originates, and a graphic indicator of sound level are displayed along with the breath sounds.